Digital Signature Standard Implementation Strategy by Optimizing Hash Functions Through Performance Optimization - Veithzal Rivai Zainal; Aziz Hakim; Ferraro S. Octora Ginting (Journal of Accounting and Finance Management, 2023)
Security method of data transmission process has been growing rapidly with the science of cryptography. Cryptography can provide security services that includes security aspects like confidentiality, data integrity, authentication and non-repudiation. Modern cryptography uses a key that must be kept secret to overcome the problem of cryptographic security. Problem in the use of the same key by two entities that communicate with each other in exchanging messages is a way to distribute the key. This problem can be overcome by using public-key cryptography, which allows users to communicate securely without a shared secret key. Digital signature is the application of public-key cryptography. When accessing important digital documents, it is necessary to verify the signature given. Implementation of digital signature always requires a hash function. Hash function used in this research namely SHA-256, SHA-384 and Tiger. Federal Information Processing Standards (FIPS) set the cryptographic standard for digital signatures is the Digital Signature Standard (DSS). Algorithms included in the DSS are the Digital Standard Algorithm (DSA), Ron Rives, Adi Shamir, and Leonard Adleman (RSA) and Elliptic Curve Digital Signature Algorithm (ECDSA). So it is necessary to test the best digital signature implementation strategy that can be used by optimizing the performance of the hash function. Performance testing of the three algorithms is done by making an application using a computer programming language C++. Implementation program using C++ class library for cryptographic scheme that is Crypto++ Library 5.6.0. Class libraries used in the classes functions for digital signatures. On the application of digital signatures generated, conducted tests is done by combining each hash function algorithm with each of the DSS in order to compare their performance in terms of time and memory usage. Against the test results are then analyzed using statistical tests. The result shows that pair of Tiger hash function and DSA algorithm is the best combination.